MANAJEMEN ORGANISASI DESA DALAM RANGKA PENYUSUNAN PERDES PELESTARIAN LINGKUNGAN HIDUP - Harini Abrilia Setyawati (Paradigma Mandiri : Jurnal Pengabdian Kepada Masyarakat, 2024)
In the context of Village Organization Management for the Formulation of Village Regulations (Perdes) on Environmental Conservation, the importance of the village's role in maintaining the sustainability of the local environment becomes the main focus. Law Number 6 of 2014 entrusts villages with the responsibility to build community welfare, enhance the self-reliance of village governments, and manage the potential and natural resources of the village. The formulation of Village Regulations (Perdes) on Environmental Conservation is a strategic step in efforts to preserve the local environment. The method used involves experiential learning, with the application of lecture methods, question and answer sessions, and the use of visuals. The results of this dedication emphasize the importance of involving various stakeholders, such as community leaders and government agencies, as well as conducting outreach and education efforts for the community. Periodic evaluations of policy implementation are also necessary to ensure the success of the program. With the cooperation of all parties, it is hoped that this policy will bring positive impacts to the environment in Argopeni Village, Ayah District, Kebumen Regency.